Semi-automatic methodology for augmented panorama development in industrial outdoor environments. (December 2017) - Gomes, Daniel Lima; dos Reis, Paulo Roberto Jansen; de Paiva, Anselmo Cardoso; Silva, Aristófanes Corrêa; Braz, Geraldo; de Araújo, Antônio Sérgio; Gattass, Marcelo
Highlights: A methodology for VR environments creation using augmented panoramas. Semi-automatic annotation of objects in augmented panoramas. A solution for remote visualization and monitoring of industrial field work. Abstract: The use of virtual reality (VR) environments based on augmented panoramas enables the creation of visualization scenarios in different application areas. These panorama-based environments significantly reduce the cost and the timeframe of developing VR applications. The use of this visualization modality in industrial environments is appropriate because in these scenarios there is little or no change of the viewable physical environment during long periods of operation. The combined use of VR concepts and augmented reality (AR) enables the creation of applications that use object detection based on image characteristics and the inclusion of information through an augmented environment. With this in mind, this paper presents a methodology for creating VR environments based on augmented panoramas that uses semi-automatic object detection using Haar-like features and real images of the operating environment. The methodology was used to create an augmented environment based on an electric power substation as a case study. This environment is used for visualizing power substation equipment variables, and it shows the possibilities of using several panorama formats for the visualization.